Failures of imagination: Racial justice in philosophy and education. (March 2022) - Frank, Jeff
This article is a retrospective look at Chris Lebron's essay 'Thoughts on Racial Democratic Education and Moral Virtue'. I argue that Lebron's work remains extremely relevant, both for its vision of antiracist education, and for the methodological questions it allows readers to contend with. As we are living in an age of increasing backlash to antiracist education, taking another look at Lebron's essay also allows us to consider the reasonableness of this backlash and what this backlash says about imagination and failures of imagination.